2020
DOI: 10.1103/physrevb.101.014441
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital excitations through the metal-to-insulator transition in Cd2Os2O7 probed with high-resolution resonant inelastic x-ray scattering

Abstract: High-resolution resonant inelastic x-ray scattering measurements (∆E = 46 meV) have been performed on Cd2Os2O7 through the metal-to-insulator transition (MIT). A weakly dispersive magnetic excitation at 120 meV evolves continuously through the MIT, in agreement with recent Raman scattering results, and provides further confirmation for an all-in, all-out magnetic ground state. Asymmetry of this feature is likely a result of coupling between the electronic and magnetic degrees of freedom. We also find that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In these theoretical studies, a sizeable single-ion anisotropy (SIA) is found along the local [111] axis, and there is even the trigonal distortion of the OsO 6 octahedron. The large SIA is experimentally confirmed, too [4,12,13]. A spin Hamiltonian with a large anisotropy was used to analyze the multiple spin-flip excitations observed in RIXS experiments [4,12] and the two-magnon continuum from Raman spectroscopy [13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In these theoretical studies, a sizeable single-ion anisotropy (SIA) is found along the local [111] axis, and there is even the trigonal distortion of the OsO 6 octahedron. The large SIA is experimentally confirmed, too [4,12,13]. A spin Hamiltonian with a large anisotropy was used to analyze the multiple spin-flip excitations observed in RIXS experiments [4,12] and the two-magnon continuum from Raman spectroscopy [13].…”
Section: Introductionmentioning
confidence: 96%
“…The large SIA is experimentally confirmed, too [4,12,13]. A spin Hamiltonian with a large anisotropy was used to analyze the multiple spin-flip excitations observed in RIXS experiments [4,12] and the two-magnon continuum from Raman spectroscopy [13]. The spin Hamiltonian used for the proceeding analysis can be written as…”
Section: Introductionmentioning
confidence: 99%
“…The driving force has been ascribed to electron correlations as well as SOIs [15,25,26]. Numerous recent experiments provide evidence for this mechanism, as well as additional intriguing phenomena such as strong spin-phonon couplings and coupled spin-charge-phonon fluctuations [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%